Hitler's religion: the twisted beliefs that drove the Third Reich - Weikart, Richard (Regnery History, 2016)
For a man whom history can never forget, Adolf Hitler remains a persistent mystery on one front--his religious faith. Atheists tend to insist Hitler was a devout Christian. Christians counter that he was an atheist. And still others suggest that he was a practicing member of the occult. None of these theories are true, says historian Richard Weikart. Delving more deeply into the question of Hitler's religious faith than any researcher to date, Weikart reveals the startling and fascinating truth about the most hated man of the 20th century: Adolf Hitler was a pantheist who believed nature was God. In Hitler's Religion , Weikart explains how the laws of nature became Hitler's only moral guide--how he became convinced he would serve God by annihilating supposedly "inferior" human beings and promoting the welfare and reproduction of the allegedly superior Aryans in accordance with racist forms of Darwinism prevalent at the time